Kilkenny dinner, December 1976 - Kilkenny Association, KILK (1976)
Black and white group portrait photograph of five women and seven men (three in clerical dress) taken at a formal event. A manuscript note on the back identifies the occasion as 'Kilkenny dinner at Bankers', Dec '76'. Photographer unknown.